d-Tubocurarine binding sites are located at alpha-gamma and alpha-delta subunit interfaces of the nicotinic acetylcholine receptor. - Pedersen, S E (1990)
The competitive nicotinic antagonist d-[3H]tubocurarine was used as a photoaffinity label for the acetylcholine binding sites on the nicotinic acetylcholine receptor (AcChoR) from Torpedo. Irradiation with 254-nm UV light of AcChoR-rich membranes equilibrated with d-[3H]tubocurarine resulted in covalent incorporation into the alpha, gamma, and delta subunits that could be blocked by alpha-bungarotoxin or by carbamoylcholine. The concentrations of d-[3H]tubocurarine required for half-maximal specific incorporation into the gamma and delta subunits were 40 nM and 0.9 microM, respectively, consistent with the dissociation constants for the high- and low-affinity binding sites (Kd = 35 nM and 1.2 microM). The concentration dependence of incorporation into alpha subunit was biphasic and consistent with labeling of both the high- and low-affinity d-tubocurarine binding sites. The specific photolabeling of each AcChoR subunit was inhibited by carbamoylcholine with appropriate dose dependence. These results establish that, in addition to the alpha subunits, the gamma and delta subunits also contribute directly to the acetylcholine binding sites and that each binding site is at an interface of subunits. Because the AcChoR subunits are homologous and are arranged pseudosymmetrically about a central axis, the photolabeling results are inconsistent with an arrangement of subunits in the AcChoR rosette of alpha beta alpha gamma delta and indicate that either the gamma or delta subunit resides between the alpha subunits.